Optimisation of Intermodal Transport Using Satellite-based Services - Nils Meyer-Larsen; Rainer Müller; Timo Köhler (Operational Excellence in Logistics and Supply Chains: Optimization Methods, Data-driven Approaches and Security Insights. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 22, 2015)
The European Space Agency (ESA) is currently funding a number of projects in order to develop services for the optimization of transport and logistics processes using satellite assets. One of these projects is I-PORT, especially addressing intermodal container transportation through European ports. In this context, one of the major challenges is the alignment in planning the arrival and departure of different modalities, e.g. vessels and trucks, such that the containers can be transferred without delays. In addition, unproductive waiting times of transport vehicles should be avoided. To support this, an integrated solution was defined and developed, which utilizes the added value of satellite assets, in particular GPS and Satellite-based AIS (Automatic Identification System). By using these services, the positions of transport vehicles are tracked and the estimated time of arrival (ETA) is calculated and regularly updated. If the I-PORT system detects a deviation from the planned schedule, e.g. a delay in arrival of a vessel, all involved actors are informed pro-actively. Consequently, the related vehicles can be re-scheduled at an early stage and waiting times and unsuccessful attempts to deliver or pick up a container can be reduced. The IPORT solution was developed based on the elaboration of user needs as well as existing technologies and services.
10419/209191; https://econpapers.repec.org/RePEc:zbw:hiclpr:22
Keywords: 650; Intermodal Container Transport; Satellite-based Services; Optimisation; ETA Prediction